Nutritional status and safety assessment on adible insect reared in Indonesia - Syabana, Rizal Andi; Yuniastri, Ratih; Matlubah, Helliyatul; Wise, Nur (Majalah Kesehatan Indonesia, 2025)
Stunting in children, pregnancy complications, and osteoporosis in the elderly remain prevalent in Indonesia, often linked to protein deficiency. This issue is particularly common among lower socio-economic groups, where limited purchasing power reduces protein consumption. The availability of protein sources is further threatened by climate change and declining environmental quality. Conventional protein sources also contribute to environmental degradation. Hence, there is a pressing need for sustainable, affordable, and environmentally friendly protein alternatives. The FAO has recognized edible insects as a viable future protein source. This study focuses on evaluating the nutritional content and food safety of three types of edible insects: mealworms, superworms, and Black Soldier Fly Larvae (BSFL). The research uses a Completely Randomized Design (CRD) with two factors: species (S) and larval condition (K). Six treatments are tested, each with three replications. Nutritional parameters assessed include carbohydrates, fats, proteins, antioxidants, and vitamins, while food safety is evaluated through microbial contamination and heavy metal analysis. Edible insects, such as mealworms, superworms, and BSFL, offer a varied nutritional profile, including protein, fat, carbohydrates, vitamin E, and antioxidants, making them a promising alternative protein source. Abstrak: Stunting pada anak, komplikasi kehamilan, dan osteoporosis pada lansia masih menjadi masalah prevalen di Indonesia, yang sering kali terkait dengan kekurangan protein. Masalah ini terutama terjadi pada kelompok masyarakat dengan status sosial ekonomi rendah, di mana keterbatasan daya beli mengurangi konsumsi protein. Ketersediaan sumber protein semakin terancam oleh perubahan iklim dan penurunan kualitas lingkungan. Sumber protein konvensional juga berkontribusi pada kerusakan lingkungan. Oleh karena itu, diperlukan alternatif protein yang berkelanjutan, terjangkau, dan ramah lingkungan. FAO telah mengakui serangga yang dapat dimakan sebagai sumber protein yang layak di masa depan. Penelitian ini bertujuan untuk mengevaluasi kandungan gizi dan keamanan pangan dari tiga jenis serangga yang dapat dimakan: mealworm, superworm, dan Black Soldier Fly Larvae (BSFL). Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan dua faktor: spesies (S) dan kondisi larva (K). Enam perlakuan diuji, masing-masing dengan tiga replikasi. Parameter gizi yang dianalisis meliputi karbohidrat, lemak, protein, antioksidan, dan vitamin, sementara keamanan pangan dinilai melalui kontaminasi mikroba dan analisis logam berat. Serangga yang dapat dimakan, seperti mealworm, superworm, dan BSFL, menawarkan profil gizi yang bervariasi, termasuk protein, lemak, karbohidrat, vitamin E, dan antioksidan, menjadikannya sumber protein alternatif yang menjanjikan.